2021
DOI: 10.1136/bmjopen-2020-045445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief exposure to misinformation about e-cigarette harms on twitter: a randomised controlled experiment

Abstract: ObjectivesTo assess the effect of exposure to misinformation about e-cigarette harms found on Twitter on adult current smokers’ intention to quit smoking cigarettes, intention to purchase e-cigarettes and perceived relative harm of e-cigarettes compared with regular cigarettes.SettingAn online randomised controlled experiment conducted in November 2019 among USA and UK current smokers.Participants2400 adult current smokers aged ≥18 years who were not current e-cigarette users recruited from an online panel. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…Details of the message stimuli selection from Twitter are described elsewhere [ 20 ]. Briefly, we conducted a keyword search of 1% of tweets relevant to e-cigarette harms on Twitter between January and September 2019 (n = 499 tweets).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the message stimuli selection from Twitter are described elsewhere [ 20 ]. Briefly, we conducted a keyword search of 1% of tweets relevant to e-cigarette harms on Twitter between January and September 2019 (n = 499 tweets).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we chose four tweets for the three conditions: (1) E-cigarettes are as or more harmful than smoking, (2) E-cigarettes are completely harmless, and (3) Uncertainty. It is important to understand the effects of exposure to Tweets that include uncertainty of e-cigarette harms, as media and public discourse around this topic have included uncertainty as evidence-based information around e-cigarette harms have been developing [ 20 ]. The control condition comprised four tweets about physical activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Exposure to misinformation about e-cigarettes can influence people’s self-reported decision to purchase them. 7 And, starting in the 1950s, major tobacco companies have sought to undermine, downplay, or discredit scientific evidence of the dangers of smoking tobacco products through aggressive marketing and public relations campaigns, 8 and likely with some success: a study in which participants were shown YouTube videos containing misleading information about tobacco products showed that people who watched such a video subsequently had more positive attitudes towards such products than a control group. 9…”
mentioning
confidence: 99%